1993
DOI: 10.1016/0304-3959(93)90078-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic hypo- and hyperalgesia: divergent effects on pain ratings and pain-related cerebral potentials

Abstract: Pain ratings and pain-related cerebral potentials in response to noxious stimuli were investigated under hypnotic hypo- or hyperalgesia. Out of a sample of 50 subjects the 10 most highly hypnotizable were selected using the Stanford Hypnotic Susceptibility Scale. Phasic pain was induced by brief electrical stimuli intracutaneously applied to the subject's left middle finger. The subjects took part in three experimental sessions. The first session was without hypnosis for familiarization with the experimental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 19 publications
3
20
0
2
Order By: Relevance
“…Hypnosis appeared more effective on the affective dimension of pain than over the sensory dimension, which is in line with other authors' fi ndings (e.g. Price, Hakins and Baker, 1987;Meier, Klucken, Soyka and Bromm, 1993;Price, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Hypnosis appeared more effective on the affective dimension of pain than over the sensory dimension, which is in line with other authors' fi ndings (e.g. Price, Hakins and Baker, 1987;Meier, Klucken, Soyka and Bromm, 1993;Price, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Further research has indicated that these late ERP components also reflect other aspects of stimulus processing, like stimulus probability and habituation, additionally supporting the notion that the magnitudes of these late ERP components more likely reflect cognitive aspects of pain processing than aspects related to the pure sensory properties of nociception~Miltner & Weiss, 1998& Weiss, , 2000 Whereas most studies of the effects of distraction on late ERP components elicited by noxious stimuli have replicated this finding, comparable studies on ERPs to painful stimuli during suggestions of hypnotic analgesia have produced rather inconsistent results. Some studies have reported decreased amplitudes of late ERP components to noxious stimuli when subjects were given hypnotic analgesia as compared to a control condition~Arendt-Nielsen, Zachariae, & Bjerring, 1990;Crawford, Pribram, & Xie, 1993!. However, other studies demonstrated no such decreases of ERP components~Meier, Klucken, Soyka, & Bromm, 1993;Miltner, Braun, & Revenstorf, 1992!. In some studies even larger ERP amplitudes were obtained during hypnotic analgesia~e.g., Sommer, 1966!. On the basis of these conflicting results, we suggest that hypnotic analgesia is not adequately explained by attentional mechanisms, but rather reflects some other information processing mechanisms.…”
mentioning
confidence: 95%
“…In addition, hypnotic suggestions alter pain sensation in both high and low susceptible subjects, but the changes are selective and somatotopically organized only in highly susceptible subjects (Benhaiem, Attal, Chauvi, Brasseur and Bouhassira, 2001) Electroencephalographic (EEG) and evoked potential (EP) studies done since the late 1970s have shown some physiological correlates refl ecting hypnotic analgesia (Halliday and Mason 1964;Meszaros, Banyai and Greguss, 1980; Barabasz and Lonsdale 1983;Spiegel, Bierre and Rootenberg, 1989; Arendt-Nielsen, Zachariae and Bjerring, 1990;Meier, Klucken, Soyka and Bromm, 1993;Zachariae and Bjerring 1994; Crawford, Knebel, Kaplan, Vendemia, Xie, Jamison and Pribram, 1998; De Pascalis, Magurano and Bellusci, 1999). In summary, these studies observed reductions in late somatosensory potentials evoked by nociceptive stimuli during hypnosis, linked to perceived pain intensity changes which seem not to be under conscious control.…”
Section: Abstract: Pain Hypnosis Fmri Pet-scan Eegmentioning
confidence: 97%